Your wish is my command programming by example - Lieberman, Henry, 1952- (San Francisco : Morgan Kaufmann Publishers, 2001)
As user interface designers, software developers, and yes-as users, we all know the frustration that comes with using "one size fits all" software from off the shelf. Repeating the same commands over and over again, putting up with an unfriendly graphical interface, being unable to program a new application that you thought of yourself-these are all common complaints. The inflexibility of today's computer interfaces makes many people feel like they are slaves to their computers. Shouldn't it be the other way around? Why can't technology give us more "custom-fitting" software? On the horizon is a new technology that promises to give ordinary users the power to create and modify their own programs. Programming by example (PBE) is a technique in which a software agent records a user's behavior in an interactive graphical interface, then automatically writes a program that will perform that behavior for the user. Your Wish is My Command: Programming by Example takes a broad look at this new technology. In these nineteen chapters, programming experts describe implemented systems showing that PBE can work in a wide variety of application fields. They include the following: The renowned authors and their editor believe that PBE will some day make it possible for interfaces to effectively say to the user, "Your wish is my command!" * Text and graphical editing * Web browsing * Computer-aided design * Teaching programming to children * Programming computer games * Geographical information systems.
Novice programming comes of age / David Canfield Smith, Allen Cypher, Larry Tesler -- Generalizing by removing detail : how any program can be created by working with examples / Ken Kahn -- Demonstrational interfaces : sometimes you need a little intelligence, sometimes you need a lot / Brad A. Myers, Richard McDaniel -- Web browsing by example / Atsushi Sugiura -- Trainable information agents for the Web / Mathias Bauer, Dietmar Dengler, Gabriele Paul -- End users and GIS : a demonstration is worth a thousand words / Carol Traynor, Marian G. Williams -- Bringing programming by demonstration to CAD users / Patrick Girard -- Demonstrating the hidden features that make an application work / Richard McDaniel -- A reporting tool using programming by example for format designation / Tetsuya Masuishi, Nobuo Takahashi -- Composition by example / Toshiyuki Masui -- Learning repetitive text-editing procedures with SMARTedit / Tessa Lau ... [et al.] -- Training agents to recognize text by example / Henry Lieberman, Bonnie A. Nardi, David J. Wright -- SWYN : a visual representation for regular expressions / Alan F. Blackwell -- Learning users' habits to automate repetitive tasks / Jean-David Ruvini, Christophe Dony -- Domain-independent programming by demonstration in existing applications / Gordon W. Paynter, Ian H. Witten -- Stimulus-response PBD : demonstrating "when" as well as "what" / David W. Wolber, Brad A. Myers -- Pavlov : where PBD meets Macromedia's Director / David Wolber -- Programming by analogous examples / Alexander Repenning, Corrina Perrone -- Visual generalization in programming by example / Robert St. Amant ... [et al.].
Includes bibliographical references and index.
Keywords: Computer programming; Electronic books